Multijet production at low xBj in deep inelastic scattering at HERA - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Jechow, M; Pavel, N; Yagües Molina, A; Antonelli, S; et al. (2007)
Inclusive dijet and trijet production in deep inelastic ep scattering has been measured for 10 < Q2 < 100  GeV2 and low Bjorken x, 10-4 < xBj < 10-2. The data were taken at the HERA ep collider with centre-of-mass energy sqrt(s) = 318  GeV using the ZEUS detector and correspond to an integrated luminosity of 82  pb-1. Jets were identified in the hadronic centre-of-mass (HCM) frame using the kT cluster algorithm in the longitudinally invariant inclusive mode. Measurements of dijet and trijet differential cross sections are presented as functions of Q2, xBj, jet transverse energy, and jet pseudorapidity. As a further examination of low-xBj dynamics, multi-differential cross sections as functions of the jet correlations in transverse momenta, azimuthal angles, and pseudorapidity are also presented. Calculations at O (αs3) generally describe the trijet data well and improve the description of the dijet data compared to the calculation at O (αs2). © 2007 Elsevier B.V. All rights reserved.